The different molecular forms of urine neutrophil gelatinase-associated lipocalin present in dogs with urinary diseases - Hsu, Wei-Li; Chiou, Hsiao-Chi; Tung, Kwong-chung; Belot, Guillaume; Virilli, Anais; Wong, Min-Liang; Lin, Fong-Yuan; Lee, Ya-Jane (BMC veterinary research, 2014)
Neutrophil gelatinase-associated lipocalin (NGAL) is a useful biomarker for the early prediction of renal diseases. NGAL may exist as monomer, dimer and/or NGAL/MMP-9 complex forms in humans. In this study, the existence of various forms of NGAL in urine (uNGAL) was determined and whether these forms are related to the different urinary diseases found in dogs is further discussed. Eighty-one urine samples from dogs with different forms of renal disease (41), pyuria (19) and a number of non-renal related diseases (10), as well as healthy dogs (11), were collected. uNGAL concentrations and their molecular forms in dogs were measured by ELISA and Western blot analysis, respectively. The uNGAL concentrations of dogs with pyuria (median: 15.35 ng/mL) were significantly higher than those of the healthy control animals (median: 3.92 ng/mL) (p < 0.01), but lower than those of dogs with renal diseases (median: 23.77 ng/mL). Each NGAL molecular form could be detected in dog urine. In particular, monomer was detected more frequently in patients with renal disease than those with non-renal diseases; while the dimer form appeared in a significantly higher percentage of cases with pyuria compared to those without pyuria. The NGAL/MMP-9 complex was found to exist not only in the patients with cystitis, but also in the cases with renal injury. Different molecular forms of uNGAL can indicate different origins of the urinary abnormalities. Determining the molecular forms of uNGAL present in diseased dogs may provide clinical workers with a tool that will help the early and more precise detection of different urinary diseases.